Environmental Pollution During MQL Machining of Alloys and Its Impact - Narinder Singh (International Journal of Advanced Science and Technology, 2020)
Machining is the process in which raw material is given desired final shape with the help of various types of operations, so it is the most important aspect of manufacturing industry. So far as machining is concerned , presently there are three types of machining which are Dry machining , Machining with Flood Lubrication and Machining with Minimum Quantity Lubrication(MQL). Except Dry machining , in other two types there is evaporation of coolant when it comes in contact with the tool and workpiece because of very high heat generation at the tool-workpiece interface . Due to evaporation of coolant , particulate matters, dust and mist are generated which cause environmental pollution. These particulate matters are very harmful for human beings. So it is underiable and should be reduced to minimum level . This paper presents a Brief study about particulate matter and its control during MQL machining of alloys.